HUBUNGAN MANAJEMEN PERTANDINGAN DENGAN TINGKAT KEPUASAN ATLET DAN KLUB SEPAKBOLA DI JAWA BARAT TAHUN 2019 - Ryan Nanda Saputra; Yudha Munajat Saputra; Nuryadi Nuryadi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2020)
This study is a study on the relationship between match management and the satisfaction level of athletes and football clubs in West Java in 2019. This study aims to determine whether there is a relationship between match management and the satisfaction level of athletes and clubs at PSSI West Java in 2019. The subject of this study is the players. and clubs that took part in the West Java competition in 2019. The method used in this research is quantitative descriptive with a correlation research design. The sample in this study amounted to 66 people, including Persib, Kabomania, Galuh fc. As for the important points in the questionnaire distributed to the 3 clubs in West Java, related to the level of satisfaction of athletes and clubs with the management of football matches in West Java. The results of this study are that there is a relationship between match management and the satisfaction level of athletes and football clubs in West Java in 2019.